(untitled) (LEARNing Landscapes, 2019)
Luke Sumich is one of the founders of Ormiston Junior College in Auckland, New Zealand. In this interview, he describes how the school came into being and the philosophy behind its personalized approach to education. He explains the views of the students and their parents as well as the challenges and hurdles encountered since the inception of the school. He concludes by offering advice for educators interested in innovative systems change.